Oral delivery of cellulose acetate phthalate-microencapsulated cholera dna vaccine - Mahlid @ Hanafi, Aimi Melati (2012)
Cholera epidemic is associated with diarrhoea and it most often results in fatal consequences. Cholera is a disease of global concern especially in areas that lack clean water supply and sanitation facilities. Current cholera vaccines provide limited term of protection; meanwhile, the development of cholera DNA vaccines may enable them to induce local mucosal as well as systemic immune response to confer long-term protection against cholera. Oral administration of cholera DNA vaccine offers potential advantage over conventional oral cholera vaccines. Oral delivery is suitable for cholera DNA vaccines because it targets the site of cholera infection which is at the mucosal surfaces in the gastrointestinal tract. Cellulose acetate phthalate (CAP) is advantageous as polymeric carriers of cholera DNA vaccine due to its enteric and nontoxic properties. CAP-microencapsulated cholera DNA vaccine may be able to provide protection for the delivery of plasmid DNA through the oral route. The study aims to formulate CAP microencapsulation for cholera DNA vaccine, and also to characterize the CAP microcapsules. This study also aims to assess the immune responses induced by CAP-microencapsulated cholera DNA vaccines in orally immunized BALB/c mice. CAP microcapsules were formulated to deliver plasmid DNA to the intestines by using solvent evaporation method. The microcapsules were characterized and were found to have an average diameter of 44.33 ± 30.22 μm, and spherical with smooth surface. The method to extract plasmid DNA from CAP was modified to study the release profile of the pDNA. The conformation of the encapsulated pDNA was found to be stable in the agarose gel electrophoresis analysis. Exposure to the acidic and basic pH conditions, which simulates the pH environment in the stomach and the intestines, showed that the release occurred in a stable manner in the former whereas it was robust in the latter. The loading capacity and encapsulation efficiency of the microcapsules, which was in the range of 2.67% - 18.33% and 1.67% - 21.3% respectively, was low. However, CAP recovery yield, which was in the range of 47.81% - 98.42%, was high which indicates that the microcapsules were efficiently formed but the loading of pDNA may be improved. In vitro transfection study showed that there was significant percentage of green fluorescent protein (GFP)-positive cells as a result of efficient transfection from CAP-encapsulated pDNA. Biodistribution studies in BALB/c mice using flow cytometry detection of GFP expression indicate that DNA was released at the stomach and intestinal regions. Female BALB/c mice were then orally immunized; ctxB expression in vivo was detected from intestinal cells and antibody responses induced were assayed using ELISA. The levels of fecal IgA peaked at week 4 with a 1.27-fold increase and serum IgG increased at week 4 and maintained at week 6 with a 1.8-fold increase. CAP microcapsules loaded with pDNA, as described in this study, may be useful as potential cholera DNA vaccine delivery to the intestines. However, more studies are needed to be focused on the design of the CAP microcapsules as a carrier for plasmid DNA.